Optimization of the design of the primary school classrooms in terms of energy and daylight performance considering occupants' thermal and visual comfort - Parnian Bakmohammadi; Esmatullah Noorzai (Energy Reports, 2020)
One of the top priorities in the building design process is minimizing energy consumption. Moreover, the~level of occupants' comfort directly affects their learning ability Therefore, this paper uses a multi-objective approach to optimize the architectural design features, including some newly examined ones, that define the geometry of a classroom. Furthermore, to create a practical methodology for minimizing lighting energy demand, we put the technique of dividing the class into independent, controllable lighting zones into practice for the first time. This research aims to introduce an optimized primary school classroom that meets both inhabitants' comfort needs and energy efficiency. For this, we first developed a parametric model using the Grasshopper plug-in for Rhino. Afterward, the environmental plug-ins of Honeybee and Ladybug were employed to evaluate energy performance and thermal comfort and find optimized solutions. The last step was assessing the occupants' visual comfort for each of these optimized solutions and selecting the final optimum designs. This two-phase optimization procedure has led to the reduction of total energy demand, up to 47.92 kWh/m2, and improvement of occupants' thermal and visual comfort. The results show that the proposed methodology can provide designers with a guideline for designing a sustainable classroom that fulfills their preferences as well as encouraging them to use innovative ways for energy conservation.
Keywords: 330; Genetic algorithm; Multi-objective optimization; Parametric design; Thermal comfort; Visual comfort